2003
DOI: 10.1002/ejic.200300067
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotetrapeptide Complexes of Nickel(II) and Palladium(II) by Template Synthesis from Dipeptide Esters with Functionalized Side Chains − Crystal Structure of [(cyclo‐Gly‐β‐Ala‐Gly‐β‐Ala‐4H+)Cu](PPN)2

Abstract: The cyclocondensations of dipeptide esters [Gly‐L‐Asp(OMe)2, Gly‐L‐Glu(OMe)2, L‐AspOMe‐β‐AlaOMe, β‐Ala‐L‐Lys(ψ‐N‐Boc,OMe), β‐Ala‐L‐Orn(ψ‐N‐Boc,OMe)] at nickel(II), palladium(II), and copper(II) templates give dianionic square‐planar complexes of deprotonated cyclotetrapeptides that contain functional groups in the side chains. The complexes with 14‐ or 16‐membered rings were isolated as [Ph3PNPPh3]+ salts. Hydrolysis of {[cyclo‐Gly‐Asp(OMe)‐Gly‐Asp(OMe)‐4H+]Pd}2− affords the tetraanionic complex [{cyclo‐Gly‐As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Insertion of one more carbon atom into the peptide cycle causes that the oxidation of the copper is observed [10]. For the peptides with greater than 13-membered rings the formation of the complex with the {4 Â N À } binding mode is preferred [8,9,11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Insertion of one more carbon atom into the peptide cycle causes that the oxidation of the copper is observed [10]. For the peptides with greater than 13-membered rings the formation of the complex with the {4 Â N À } binding mode is preferred [8,9,11].…”
Section: Introductionmentioning
confidence: 97%
“…The previous studies on the binding abilities of cyclopeptides towards Cu(II) ions [5][6][7][8][9][10][11] showed that His-containing cyclopeptides are able to bind copper(II) tightly through imidazole as well as amide nitrogens. The pH and the peptide ring size have a great impact on the kind of the coordinated nitrogens.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclocondensation of various non activated dipeptide esters (also those with functionalized side chains) could be achieved at Ni II , Pd II , or Cu II templates to give dianonic square‐planar complexes of deprotonated cyclotetrapeptides 7 47,48 (Scheme ). From steric reasons these template reactions proceed favorably with dipeptide esters, which contain α‐ and β‐amino acids to give finally complexes with a 14 membered cyclopeptide (e.g.…”
Section: Template Synthesis Of Cyclotetrapeptide Complexes Of Niiimentioning
confidence: 99%
“…The dianionic tetrapeptide palladium complex from Gly‐ L ‐Asp(OMe) 2 was hydrolyzed to give the tetraanionic complex [Pd(cyclo‐Gly‐Asp‐Gly‐Asp‐6H + )] 4– . Also cyclopeptide complexes from the dipeptide esters β‐Ala‐l‐Lys(ω‐NBoc)OMe and β‐Ala‐ L ‐Orn(ω‐NBoc)OMe were synthesized 48. The free cyclo‐tetrapeptides can be cleaved from the metal ion by HCl in methanol.…”
Section: Template Synthesis Of Cyclotetrapeptide Complexes Of Niiimentioning
confidence: 99%
“…23 The affinity of Ni for dipeptide esters can be utilized in the metal-ion templated synthesis of cyclotetrapeptides. 24 Our group is interested in the coordination chemistry of dinuclear nickel complexes supported by the hexaaza-dithiophenolato macrocycle (L) 2− ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%